Rekonstruksi Konsep Kartu Kredit Syariah: Integrasi Fiqh Muamalah dan Teknologi Keuangan Modern - Nasution, Gita Puspa Chandrika; Matondang, Nur Hayyun; Nasution, Nur Sakinah; Tanjung, Paulina Sari; Pasaribu, Nurainun; Dasopang, Nursania (Jurnal Bisnis dan Ekonomi Islam, 2025)
The development of modern financial technology encourages the need to reconstruct the concept of Islamic credit cards in order to be able to answer the challenges of sharia compliance, digital innovation, and the needs of Muslim consumers in the digital economy era. This research aims to formulate an integration model of sharia credit card reconstruction between classical fiqh muamalah and modern financial technology, especially through the renewal of kafalah, qardh, and ijarah/ujrah contracts in the digital ecosystem. The research method uses a library research approach with qualitative-descriptive analysis, including the examination of primary sources of fiqh muamalah, DSN-MUI fatwa, AAOIFI and IFSB standards, as well as international sharia fintech literature. The results of the study show that the reconstruction of Islamic credit cards requires a redefinition of the concept, strengthening the contract structure, and the integration of AI-based technology, blockchain, and real-time sharia compliance engines. The kafalah contract is reconstructed through real-time halal merchant verification and automated sharia screening; the qardh contract is strengthened through a blockchain-based digital ledger and sharia reminder feature; and the ijarah contract is developed through usage-based ujrah and smart contract validation. The analysis also found four main challenges: low Islamic financial literacy, regulatory insynchronization, delay in technology adoption, and suboptimal product competitiveness. This study concludes that the reconstruction of sharia credit cards must be built through sharia-based integrative solutions–technology, harmonization of global regulations, and the development of the sharia digital ecosystem 4.0. This model can be the foundation for the development of competitive, secure, and sustainable Islamic payment instruments. Perkembangan teknologi keuangan modern mendorong perlunya rekonstruksi konsep kartu kredit syariah agar mampu menjawab tantangan kepatuhan syariah, inovasi digital, dan kebutuhan konsumen Muslim di era ekonomi digital. Penelitian ini bertujuan merumuskan model rekonstruksi kartu kredit syariah berbasis integrasi antara fiqh muamalah klasik dan teknologi keuangan modern, khususnya melalui pembaruan akad kafalah, qardh, dan ijarah/ujrah dalam ekosistem digital. Metode penelitian menggunakan pendekatan library research dengan analisis kualitatif-deskriptif, mencakup telaah sumber primer fiqh muamalah, fatwa DSN-MUI, standar AAOIFI dan IFSB, serta literatur fintech syariah internasional. Hasil penelitian menunjukkan bahwa rekonstruksi kartu kredit syariah membutuhkan redefinisi konsep, penguatan struktur akad, dan integrasi teknologi berbasis AI, blockchain, dan real-time sharia compliance engine. Akad kafalah direkonstruksi melalui real-time halal merchant verification dan automated sharia screening; akad qardh diperkuat melalui blockchain-based digital ledger dan fitur pengingat syariah; serta akad ijarah dikembangkan melalui usage-based ujrah dan validasi smart contract. Analisis juga menemukan empat tantangan utama: rendahnya literasi keuangan syariah, ketidaksinkronan regulasi, keterlambatan adopsi teknologi, dan daya saing produk yang belum optimal. Penelitian ini menyimpulkan bahwa rekonstruksi kartu kredit syariah harus dibangun melalui solusi integratif berbasis syariah–teknologi, harmonisasi regulasi global, dan pengembangan ekosistem digital syariah 4.0. Model ini dapat menjadi fondasi bagi pengembangan instrumen pembayaran syariah yang kompetitif, aman, dan berkelanjutan.